Assessing Teacher Burnout, Qualifications and Experience on Teacher Effectiveness in Secondary Schools - Gorain, Shishupal; Ghosh, Soumen (PT. Riset Press International, 2025)
The study aimed to assess Teacher Burnout (Personal Accomplishment, Emotional Exhaustion and Depersonalization), qualifications, and experience, as well as its effectiveness among secondary school teachers in the Purulia district of West Bengal, India. A sample of 100 secondary school teachers was selected using a purposive sampling technique. Statistical analyses, including t-tests, correlation, and linear regression, were used to analyse the data. The study revealed that highly qualified teachers were more effective, while less experienced teachers demonstrated effectiveness, particularly in adopting innovative teaching methods in alignment with the feedback. This study has found that personal accomplishment showed a strong positive correlation with teacher effectiveness, highlighting the importance of strategies to mitigate burnout factors. While emotional exhaustion and depersonalization did not directly impact effectiveness, its’ addressed burnout contributors are crucial for optimal performance. The educational implications are that hiring and retaining highly experienced teachers first and establishing mentorship programs to assist less experienced teachers are recommended. The study concludes that burnout significantly diminishes the effectiveness of teachers by impairing cognitive function, emotional regulation and overall job performance.